2007
DOI: 10.1002/eji.200737409
|View full text |Cite
|
Sign up to set email alerts
|

IL‐23 and the Th17 pathway promote inflammation and impair antifungal immune resistance

Abstract: Although inflammation is an essential component of the protective response to fungi, its dysregulation may significantly worsen fungal diseases. We found here that the IL‐23/IL‐17 developmental pathway acted as a negative regulator of the Th1‐mediated immune resistance to fungi and played an inflammatory role previously attributed to uncontrolled Th1 cell responses. Both inflammation and infection were exacerbated by a heightened Th17 response against Candida albicans and Aspergillus fumigatus, two major human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
496
3
6

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 506 publications
(537 citation statements)
references
References 41 publications
26
496
3
6
Order By: Relevance
“…Our findings corroborate those of others showing that IL-17 potentiates in vitro neutrophil killing of pneumococcus (55). However, they are in apparent contradiction with the demonstration that IL-17 reduces neutrophil antifungal activity (56). The use of different neutrophil microbial targets may explain the observed differences.…”
Section: Discussionsupporting
confidence: 77%
“…Our findings corroborate those of others showing that IL-17 potentiates in vitro neutrophil killing of pneumococcus (55). However, they are in apparent contradiction with the demonstration that IL-17 reduces neutrophil antifungal activity (56). The use of different neutrophil microbial targets may explain the observed differences.…”
Section: Discussionsupporting
confidence: 77%
“…28 We found that the rs11209026 variant in donor was associated with decreased risk of fungal infections and, IL-23/Th17 genetic variants in transplantation A Carvalho et al in patient, with improved OS, a finding consistent with the protective effects of IL-23 signaling attenuation in experimental aspergillosis. 25 The fact that donor rs11209026 also increased the risk of CMV infection, while consistent with the enhancing role of IL-23 of antiviral immunity, 39 indicates that fungal more than CMV infection may impact on OS in our cohort of patients. Although the variant could arguably influence OS by modifying the incidence of disease relapse or GVHD, a beneficial effect on relapse was only demonstrated in the univariate analysis and no effect on GVHD was found whatsoever.…”
Section: Discussionsupporting
confidence: 68%
“…19 It appears that an imbalance between Th17 and regulatory T cells (Treg) ultimately associates with the development of transplant rejection. 20,21 Considering that the role of Th17 cells in protection vs pathology in infectious diseases is also controversial, with protective 11,22,23 and detrimental 12,24,25 effects being reported, it follows that genetic variants affecting the expression of cytokines of the IL-23/Th17 pathway may have a role in transplantation outcome.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is also evidence that IL-23 and IL-17 may have a negative role in immunity to fungal infection. IL-23p19 À/À mice were less susceptible to intragastric infection with C. albicans and intranasal infection with Aspergillus fumigatus and this was associated with enhanced IL-12 and IFN-g production [94]. This study concluded that IL-23 and IL-17 impaired the anti-fungal immunity by suppressing Th1 responses and the fungicidal activity of neutrophils.…”
Section: Role Of Il-17-secreting T Cells In Infectionmentioning
confidence: 72%
“…IFN-g may also play a role in controlling pathogenic T cells in autoimmunity by inducing peripheral conversion of CD4 1 CD25 À T cells into CD4 1 FoxP3 1 Treg cells [102]. While all these reports suggest that IFN-g may suppress induction of Th17 cells, there is also evidence that IL-23 and IL-17 may negatively regulate IFN-g production; anti-IL-23 and anti-IL-17 enhanced IFN-g production in mice with fungal infections [94]. It has also been demonstrated that IFN-g can enhance IL-23p19 and IL-12p40 mRNA, whereas IL-4 suppresses IL-12p19 and IL-12p40 in response to Sendai virus infection [103].…”
Section: Regulation Of Il-17-secreting T Cellsmentioning
confidence: 99%